(3GdTaG HJYQja Mbhb GdeUWais - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3MSjf s)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HESeg GdCSei GdeNJU HGdedc GdCYR GdCYei CeG HYO CTQa Gddg bdHi hbdHc HCfhGQ Gdjbjf hdWa di HeG dWa Hg dChdjGFg GdeJbjf GdPjf TQage HfRd bOSg s
(3BNQgG (B:s
(3hjMTQfG ai GdQYjd GdChd hCgd GdHGH GdCjef ef Cgd TaGYJg hfMeOg Ydi gOi Edjg ef LeYg fLR cJGH GdTaG HJYQja Mbhb GdeUWai Udi Gddg Ydjg hSde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1052s
Keywords: (3GdMOjK h GdeUWdMs